Investigating the link between post-tuberculosis lung disease (PTLD) and circulatory biomarkers in a South African cohort - Jumaar, Chrisstoffel (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.